Insights into post-growth doping and proposals for CdTe:In photovoltaic devices. (1st October 2022) - Thomas, Luke; Hobson, Theo D C; Phillips, Laurie J; Cheetham, Kieran J; Tarbuck, Neil; Jones, Leanne A H; Smiles, Matt J; Don, Chris H; Thakur, Pardeep K; Isaacs, Mark; Shiel, Huw; Campbell, Stephen; et al.
Abstract: This paper is motivated by the potential advantages of higher doping and lower contact barriers in CdTe photovoltaic devices that may be realized by using n-type rather than the conventional p-type solar absorber layers. We present post-growth doping trials for indium in thin polycrystalline CdTe films using the diffusion of indium metal with indium chloride. Chemical concentrations of indium up to 10 19 cm −3 were achieved and the films were verified as n-type by hard x-ray photoemission. Post-growth chlorine treatment (or InCl3 ) was found to compensate the n-doping. Trial structures comprising CdS/CdTe:In verified that the doped absorber structures performed as expected both before and after chloride treatment, but it is recognized that this is not an optimum combination. Hence, in order to identify how the advantages of n-type absorbers might be fully realized in future work, we also report simulations of a range of p–n junction combinations with n-CdTe, a number of which have the potential for high V oc .